Bifunctional catalytic isomerization of decane over MTT-type aluminosilicate zeolite crystals with siliceous rim - Huybrechts, Ward; Thybaut, Joris W.; De Waele, Bart R.; Vanbutsele, Gina; Houthoofd, Kristof J.; Bertinchamps, Fabrice; Denayer, Joeri F.M.; Gaigneaux, Eric M.; Marin, Guy B.; Baron, Gino V.; Jacobs, Pierre A.; Martens, Johan A. (Journal of catalysis, 2006)
Micrometer-size MTT-type zeolite crystals with aluminum depletion in the outer layer were synthesized. The compositional variation in individual crystals was obtained by altering the chemical composition of the gel during crystal growth of MTT-type zeolite. Chemical composition of the bulk and the surface of the crystals was determined using 27Al MAS NMR and XPS, respectively. The zeolite with siliceous rim was converted into a bifunctional catalyst by neutralizing the cation-exchange capacity with protons and plating with a trace amount of platinum metal. The MTT zeolite with siliceous crystal termination was catalytically much less active than the isostructural ZSM-23 zeolite with homogeneous chemical composition. The catalytic activity reflects the aluminum content on the surface of the crystals determined by XPS, rather than the bulk composition. The reaction mechanism and the reaction kinetics were analyzed using a microkinetic model developed previously for the structurally related TON-type zeolite. The catalytic data are in favor of the pore mouth catalysis model of skeletal isomerization of long n-alkanes on 10-membered ring tubular pore zeolites.